KUALITAS PELAYANAN POSYANDU DI KECAMATAN GUNUNG GURUH KABUPATEN SUKABUMI - Hendraningsih, Ratih; Liliawati, Lia; Arief Firman Nurdin, Mochamad; Mita Afriani (STISIP Widyapuri Mandiri Sukabumi, 2025)
Service quality is the main benchmark in the success of a public service. Posyandu is one of the public service providers for the community. The purpose of this study is to evaluate the services of posyandu cadres in providing services to the community, to find out the achievement of the results of cadre services compared to the expectations of the community regarding information literacy, parenting and professionalism of cadres. This study uses the SERVQUAL method where in this method objects are measured using dimensions such as tangible, reliability, responsiveness, assurance and empathy. The object of this study is the cadres of posyandu in Gunung Guruh District as many as 74 posyandu spread across 5 villages. The total population in this study is 4,395 mothers of infants/toddlers and pregnant women with a sample of 97 mothers of babies/toddlers and pregnant women. The results of the study showed that from the five dimensions of service, there was a gap between perception and average expectations of -0.299 with an average percentage of perception achievement of 93.24%. The lowest percentage is found in the physical evidence dimension (tangible) with a perception achievement of 85.65 with a gap of -0.631, in this physical evidence dimension shows several indicators that must be improved. Meanwhile, the achievement of perception of the other four dimensions is above 90%.